Evaluasi Program Pendidikan Kesetaraan Paket C Berbasis Model CIPP di PKBM Cerdik - Anggriani, Mita; Khoiruumah, Ilma; Aulia, Lidiana; Nurmaulida, Astrid (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
The lack of citizen participation in PKBM Cerdik will hinder program evaluation. The purpose of conducting a program evaluation is to find out the achievement of program objectives by measuring the implementation of program activities. One of the evaluations that can be carried out is through the CIPP evaluation, this evaluation is comprehensive in nature which is reviewed not only based on results but through the dimensions of context, input, process and product. This research was conducted using a qualitative approach. Data were obtained directly from observations and interviews with research objects, namely learning residents, tutors, and managers. While secondary data includes documentation on the package C equality program. One of the things included in the CIPP evaluation is from the existing infrastructure at PKBM Cerdik, namely the availability of several studios, including a music studio, graphic design studio and others. Where this studio is made so that learning residents have additional skills according to their interests and talents. the researcher suggests to always monitor and provide training for both permanent and volunteer tutors so that they continue to make updates so that learning can be carried out effectively and efficiently. The use of elaborative learning methods needs to be considered regarding its readiness, tutors must be able to keep up with the times so that the methods used can attract the attention of learning residents.